Limited Attention, Marital Events, and Hedge Funds - LU, Yan (Institutional Knowledge at Singapore Management University, 2015)
We explore the impact of limited attention on investment performance by analyzing the returns of hedge fund managers who are distracted by personal events such as marriage and divorce. We find that marriages and divorces are associated with significantly lower fund alpha, during the six-month period surrounding the event and for up to two years after the event. Relative to the pre-event window, fund alpha falls by an annualized 8.50 percent during a marriage and 7.39 percent during a divorce. Busy fund managers who manage larger funds and engage in high tempo investment strategies are more affected by marriage. Fund managers who depend on interpersonal relationships in their investment strategies are more affected by divorce. We show that behavioral biases may partially explain the connection between inattention and performance deterioration. The difference between the proportion of gains realized and the proportion of losses realized widens during a marriage and a divorce, indicating that inattentive hedge fund managers are more prone to the disposition effect. Taken together, our findings suggest that limited investor attention can hurt the investment performance of professional money managers.